Extracellular cold-inducible RNA-binding protein in CNS injury: molecular insights and therapeutic approaches - Dmitriy Lapin; Archna Sharma; Ping Wang (Journal of Neuroinflammation)
Abstract Central nervous system (CNS) injuries, such as ischemic stroke (IS), intracerebral hemorrhage (ICH) and traumatic brain injury (TBI), are a significant global burden. The complex pathophysiology of CNS injury is comprised of primary and secondary injury. Inflammatory secondary injury is incited by damage-associated molecular patterns (DAMPs) which signal a variety of resident CNS cells and infiltrating immune cells. Extracellular cold-inducible RNA-binding protein (eCIRP) is a DAMP which acts through multiple immune and non-immune cells to promote inflammation. Despite the well-established role of eCIRP in systemic and sterile inflammation, its role in CNS injury is less elucidated. Recent literature suggests that eCIRP is a pleiotropic inflammatory mediator in CNS injury. eCIRP is also being evaluated as a clinical biomarker to indicate prognosis in CNS injuries. This review provides a broad overview of CNS injury, with a focus on immune-mediated secondary injury and neuroinflammation. We then review what is known about eCIRP in CNS injury, and its known mechanisms in both CNS and non-CNS cells, identifying opportunities for further study. We also explore eCIRP’s potential as a prognostic marker of CNS injury severity and outcome. Next, we provide an overview of eCIRP-targeting therapeutics and suggest strategies to develop these agents to ameliorate CNS injury. Finally, we emphasize exploring novel molecular mechanisms, aside from neuroinflammation, by which eCIRP acts as a critical mediator with significant potential as a therapeutic target and prognostic biomarker in CNS injury.